SECONDARY IMMUNITY RESPONSE OF MENCIT BALB / C (MUS MUSCULUS) EXPORTED BALI COW TESTISICULAR EXTRACT (BOS SONDAICUS) - Primawati, Sri Novita (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2013)
Based on previous research by observing leukosit ploriferation of Balb / c mice given Balinese cow testical extract which showed significant result on observation to 72 hours after injection, while at 3 hours and 24 hours is not significant, it is suspected that the immunological response given to testicular extract a secondary immune response. This study aims to determine the ploriferation of Balb / c mice leukocytes exposed at some observation time, whether these include primary or secondary immune responses. Therefore it is necessary to do further research by adding exposure time of 1 day, 3 days, 5 days, and 7 days with only one exposure Con A (at 0 hour only). This study was designed with a complete randomized factorial design. The data obtained were analyzed by ANOVA analysis using F test. The results of this study showed that the influence of immunosuppression was highest on the third day (72 hours) and disappeared on the seventh day. This shows that the immunological response shown during observation of leukocyte proliferation of Balb / c mice is a secondary response.